FOTOREDUKSI Cd (II) MENGGUNAKAN KATALIS TiO2 DENGAN SENSITIZER KLOROFIL YANG DIAKTIVASI SINAR MATAHARI - Uyi Sulaeman; Kapti Riyani; Anung Riapanitra; Dyah Indriastuti (Universitas Jenderal Soedirman, 2007)
The photoreduction of Cd (II) has been investigated using thin layer catalyst of titanium dioxide and chlorophyll as sensitizer. Thin layer catalyst could be prepared by sol gel method deposited on glass slide. The treatments of experimental are: TiO2 catalyst using chlorophyll without sunlight illumination, TiO2 catalyst using chlorophyll with sunlight illumination and TiO2 catalyst with sunlight illumination. The concentration of Cd (II) in the solution is monitored every 30 minutes until 150 minutes illuminations by atomic absorption spectroscopy. The results showed that concentration of Cd (II) decreased reached to 45,53 % in TiO2 catalyst using chlorophyll with sunlight illumination at pH 5 after 150 minutes illumination and it decreased reached to 34.07% at pH 7 after 120 minutes illumination. Addition the chlorophyll to TiO2 catalyst increased photoreduction activities.